Analysis of Pre-Elderly Workers’ Quality Index and Its Impact on East Java’s Economy (Nighttime Light Approach): Reflection on Silver Economy Potential - Fuad Ramdhan Dewantoro; Abyan Rai (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2026)
BPS projection (2023) indicates that the proportion of elderly in East Java will rise from 15.40% (2025) to 25.41% (2050), surpassing national average. Aging population presents both challenges and opportunities, particularly in the potential of silver economy focused on production, consumption, and marketing of goods and services for elderly (60+) and pre-elderly (45–59). Without proper strategies, aging population can burden economy through declining productivity, rising health costs, and pensions. Low quality of elderly workers (formality 13.17%, senior high education 12.18%, income above 2.5 million 17.55%) and pre-elderly workers (TPAK 83.5% yet low quality) exacerbates negative impacts. Improving worker quality needs attention starting from pre-elderly phase to mitigate risks of aging population. This study analyzes Pre-Elderly Worker Quality Index and its impact on East Java’s economy using Nighttime Light (NTL) approach to reflect potential of silver economy in addressing aging population. Index construction through factor analysis of 12 variables (SAKERNAS 2021–2023) shows a shift of determinants from work conditions (2021) to digital capacity, education, and training (2022–2023), with health as consistent factor. K-Means Cluster analysis groups East Java districts/cities into two clusters: cluster 1 with limited silver economy potential (district areas including Tapal Kuda/Madura, low pre-elderly worker quality and economy) and cluster 2 with promising silver economy potential (urban/industrial, high pre-elderly worker quality and economy). Spatial panel regression (SAR-FEM) confirms significant positive effect of quality index on economic indicators (NTL, GRDP, and local revenue), while pre-elderly TPAK has negative effect, emphasizing quality over participation. NTL approach proves effective in capturing microeconomic dynamics. Recommendations include strengthening digital literacy, education, training, preventive health, job formalization, and development of industries supporting silver economy to reduce inequality and optimize sustainable economic growth.